Assimilation of some consonants at word boundaries - Kalašinskaitė-Zavišienė, Eidmantė (Baltistica, 2023)
Research on phonetic processes in coherent speech is important for formulating recommendations for the phonetic transcription of texts, teaching Lithuanian pronunciation to native and non-native speakers, and developing language technology products such as recognizers and synthesizers. However, the coarticulation of sounds in Lithuanian is not well-studied. The purpose of this study was to identify the most important regularities of word-boundary consonant assimilation according to the activity of vocal cords and the place of articulation. The object of the study was the voiceless stop consonants [k], [p], [t] and the fricative consonants [s], [ʃ] at the end of words. The empirical material consisted of 32 word combinations, which were read by 20 speakers three times at a normal and fast pace. To determine consonant assimilation according to vocal cords, the percentage of voicelessness was calculated, the place of articulation assimilation was studied based on the spectrum centroid, and degemination was investigated by examining duration. All parameters were set using the sound analysis program Praat. The study allows us to draw the following conclusions: (a) at word boundaries before voiced consonants, voiceless consonants become voiced, (b) fricative dental and alveolar consonants at word boundaries undergo the assimilation of the place of articulation, (c) degemination does not always accompany the place of the articulation assimilation of consonants. No clear correlations were observed between the number of syllables in the analyzed words and the degree of assimilation, which suggests that in coherent speech, phonetic processes are not stopped by word boundaries, but by the boundaries of larger units – phonological phrases.